Elevation and grassland cover shape natural enemy communities in the Kenyan maize crops - Grace Mercy Amboka; Maryselah Nelima; Charles A.O. Midega; Daniel Munyao Mutyambai; Benjamin Feit; Mattias Jonsson (International Journal of Tropical Insect Science, 2025)
Natural enemies, including arthropod predators and parasitoids, provide essential pest control services in agricultural systems by reducing pest populations. However, studies examining how natural enemies respond to environmental gradients, such as elevation and grass cover, are limited in sub-Saharan Africa. This study investigates the effect of elevation (1150–1970 m above sea level) and grassland cover in the surrounding landscape (2–30%) on natural enemy communities in maize fields in western Kenya over two consecutive sampling seasons. We selected maize fields along gradients of elevation and percentage of grassland and conducted field surveys using pitfall traps to assess the diversity and composition of natural enemies. Natural enemy diversity, richness, evenness, abundance and community composition were compared across gradients using Generalised Linear Mixed Models and Non-Metric Multidimensional Scaling. Across gradients, ants were the most abundant predator group. Lower elevations supported natural enemy communities with higher evenness, while higher elevations were dominated by Myrmicaria ants. Grassland cover had limited overall effects, with a non-significant but positive association with species richness. Notably, community composition shifted along the elevational gradient, with Myrmicaria ants being less dominant < 1600 masl. Their dominance at high elevations, where grass cover is lower, may reduce overall pest control resilience, as low evenness and reliance on a single genus diminish functional redundancy. This underscores the need for integrated pest management strategies that consider multiple environmental variables. Overall, our findings highlight the importance of environmental gradients in shaping natural enemy biodiversity in agricultural fields with implications for pest control in western Kenya.

Functional redundancy of weed seed predation is reduced by intensified agriculture - Eirini Daouti; Veronika Neidel; Benjamin Carbonne; Hana Vašková; Michael Traugott; Corinna Wallinger; Riccardo Bommarco; Benjamin Feit; David A. Bohan; Pavel Saska; Jiří Skuhrovec; Sasha Vasconcelos; et al. (Ecology Letters, 2024)
Intensified agriculture, a driver of biodiversity loss, can diminish ecosystem functions and their stability. Biodiversity can increase functional redundancy and is expected to stabilize ecosystem functions. Few studies, however, have explored how agricultural intensity affects functional redundancy and its link with ecosystem function stability. Here, within a continental‐wide study, we assess how functional redundancy of seed predation is affected by agricultural intensity and landscape simplification. By combining carabid abundances with molecular gut content data, functional redundancy of seed predation was quantified for 65 weed genera across 60 fields in four European countries. Across weed genera, functional redundancy was reduced with high field management intensity and simplified crop rotations. Moreover, functional redundancy increased the spatial stability of weed seed predation at the field scale. We found that ecosystem functions are vulnerable to disturbances in intensively managed agroecosystems, providing empirical evidence of the importance of biodiversity for stable ecosystem functions across space.

Climate change and ecological intensification of agriculture in sub-Saharan Africa – A systems approach to predict maize yield under push-pull technology - Nikolaos Alexandridis; Benjamin Feit; Job Kihara; Tim Luttermoser; Wilhelm May; Charles Midega; Ingrid Öborn; Katja Poveda; Gudeta W. Sileshi; Beyene Zewdie; Yann Clough; Mattias Jonsson (Agriculture, Ecosystems & Environment, 2023)

Negative frequency dependent prey selection by two canid predators and its implications for the conservation of a threatened rodent in arid Australia - Elizabeth L. Sheldon; Benjamin Feit; Anna Feit; Mike Letnic (Biodiversity and Conservation, 2023)
Unprecedented anthropogenic changes to biodiversity and biogeography demand a greater understanding of the consequences of altered faunal composition for ecosystem functioning. Selective predation has important, yet poorly understood effects on ecosystem stability, and can be strongly influenced by the relative frequencies of different prey types in the environment. Yet, how predators adjust their selection for prey according to their environmental frequency is often overlooked. Here, we assessed frequency dependent selection of prey by dingoes and foxes in the Australian desert, biannually, across a nine-year period (2007–2016). Both predators exhibited potentially destabilizing, negative frequency dependent selection for prey. Foxes persisted to preferentially consume a threatened, native rodent ( Notomys fuscus ) when it was environmentally scarce. Bolstered by the observation that N.fuscus occurs at low densities in areas where foxes are common, our results suggest that N.fuscus is particularly vulnerable to predation by this predator; possibly because it is naïve and/or lacks adaptations to avoid or escape predation by the relatively recently introduced fox. Dingoes tended to consume reptiles when they were scarce; potentially constituting a conservation concern if selected reptilian taxa are threatened. Foxes avoided, thus were unlikely to control populations of overabundant kangaroos, while both foxes and dingoes showed a preference for, and may therefore control populations of invasive rabbits. The integration of our results into the relative suites of (de)stabilizing influences exerted by dingoes and foxes is important to provide a more dynamic insight into how each predator impacts their naturally fluctuating ecosystems.

A trophic cascade initiated by an invasive vertebrate alters the structure of native reptile communities - Benjamin Feit; Tim Dempster; Tim S. Jessop; Jonathan K. Webb; Mike Letnic (Global Change Biology, 2020)
Invasive vertebrates are frequently reported to have catastrophic effects on the populations of species which they directly impact. It follows then, that if invaders exert strong suppressive effects on some species then other species will indirectly benefit due to ecological release from interactions with directly impacted species. However, evidence that invasive vertebrates trigger such trophic cascades and alter community structure in terrestrial ecosystems remains rare. Here, we ask how the cane toad, a vertebrate invader that is toxic to many of Australia's vertebrate predators, influences lizard assemblages in a semi‐arid rangeland. In our study area, the density of cane toads is influenced by the availability of water accessible to toads. We compared an index of the abundance of sand goannas, a large predatory lizard that is susceptible to poisoning by cane toads and the abundances of four lizard families preyed upon by goannas (skinks, pygopods, agamid lizards and geckos) in areas where cane toads were common or rare. Consistent with the idea that suppression of sand goannas by cane toads initiates a trophic cascade, goanna activity was lower and small lizards were more abundant where toads were common. The hypothesis that suppression of sand goannas by cane toads triggers a trophic cascade was further supported by our findings that small terrestrial lizards that are frequently preyed upon by goannas were more affected by toad abundance than arboreal geckos, which are rarely consumed by goannas. Furthermore, the abundance of at least one genus of terrestrial skinks benefitted from allogenic ecosystem engineering by goannas where toads were rare. Overall, our study provides evidence that the invasion of ecosystems by non‐native species can have important effects on the structure and integrity of native communities extending beyond their often most obvious and frequently documented direct ecological effects.

Apex Predators Decouple Population Dynamics Between Mesopredators and Their Prey - Benjamin Feit; Anna Feit; Mike Letnic (Ecosystems, 2019)

Resilience of ecosystem processes: a new approach shows that functional redundancy of biological control services is reduced by landscape simplification - Benjamin Feit; Nico Blüthgen; Michael Traugott; Mattias Jonsson (Ecology Letters, 2019)
Functional redundancy can increase the resilience of ecosystem processes by providing insurance against species loss and the effects of abundance fluctuations. However, due to the difficulty of assessing individual species’ contributions and the lack of a metric allowing for a quantification of redundancy within communities, few attempts have been made to estimate redundancy for individual ecosystem processes. We present a new method linking interaction metrics with metabolic theory that allows for a quantification of redundancy at the level of ecosystem processes. Using this approach, redundancy in the predation on aphids and other prey by natural enemies across a landscape heterogeneity gradient was estimated. Functional redundancy of predators was high in heterogeneous landscapes, low in homogeneous landscapes and scaled with predator specialisation. Our approach allows quantifying functional redundancy within communities and can be used to assess the role of functional redundancy across a wide variety of ecosystem processes and environmental factors.

Invasive cane toads might initiate cascades of direct and indirect effects in a terrestrial ecosystem - Benjamin Feit; Christopher E. Gordon; Jonathan K. Webb; Tim S. Jessop; Shawn W. Laffan; Tim Dempster; Mike Letnic (Biological Invasions, 2018)

Invasive Cane Toads’ Predatory Impact on Dung Beetles is Mediated by Reservoir Type at Artificial Water Points - Benjamin Feit; Tim Dempster; Heloise Gibb; Mike Letnic (Ecosystems, 2015)

Species level traits determine positive and negative population impacts of invasive cane toads on native squamates - Benjamin Feit; Mike Letnic (Biodiversity and Conservation, 2015)